Glycan-dependent and -independent Interactions Contribute to Cellular Substrate Recruitment by Calreticulin - Wijeyesakere, Sanjeeva J. (American Society for Biochemistry and Molecular Biology, 2013)
Calreticulin is an endoplasmic reticulum chaperone with specificity for monoglucosylated glycoproteins. Calreticulin also inhibits precipitation of nonglycosylated proteins and thus contains generic protein-binding sites, but their location and contributions to substrate folding are unknown. We show that calreticulin binds glycosylated and nonglycosylated proteins with similar affinities but distinct interaction kinetics. Although both interactions involve the glycan-binding site or its vicinity, the arm-like proline-rich (P-) domain of calreticulin contributes to binding non/deglycosylated proteins. Correspondingly, ensemble FRET spectroscopy measurements indicate that glycosylated and nonglycosylated proteins induce “open” and “closed” P-domain conformations, respectively. The co-chaperone ERp57 influences substrate-binding kinetics and induces a closed P-domain conformation. Together with analysis of the interactions of calreticulin with cellular proteins, these findings indicate that the recruitment of monoglucosylated proteins to calreticulin is kinetically driven, whereas the P-domain and co-chaperone contribute to stable substrate binding. Substrate sequestration in the cleft between the glycan-binding site and P-domain is a likely mechanism for calreticulin-assisted protein folding.